الحديث الصحيح عند الإمام الحاكم - نيد, نعيمة (University of Eloued جامعة الوادي, 2018)
"ملخص الدراسة يتمحور موضوع هذه الدراسة حول معرفة الحديث الصحيح عند الإمام الحاكم، ففيها سنقوم بدراسة نوع معين من أنواع علوم الحديث عند هذا العالم، ويترتب على هذا ترجمة للإمام الحاكم، ومعرفة شرطه في الصحيح، من خلال كتبه وأقوال الأئمة، والتطرق لدراسة شروط الصحيح الخمسة كل واحد على حدا، ثم نختمها بدراسة نماذج من تصحيحات الحاكم للأحاديث وهل وافقه غيره من الأئمة أم لا، والله ولي التوفيق. " "Summary This subject is about a study of the perception of the authentic citation of Imam Al-Hakem. We will study a particular aspect in the field of modern science to this scientist. This will result to the interpretation of Imam Al-Hakem، and knowing his condition in his authenticity، throughout his writings and citations of Other Imams. We presented the conditions of study of the five authentics، each one separately. We ended this study with samples of corrections of Al-Hakem to the citations and whether others Imams agreed with him or not.God grants success."
مذكرة ماستر تخصص علوم الحديث
Keywords: الحديث الصحيح- الامام الحاكم- الاشتراط; The correct Hadith - the ruling Imam - the requirement